Geotechnical factors influencing earth retaining wall deformation during excavations - Seo, Seunghwan; Park, Jongjeon; Ko, Younghun; Kim, Gunwoong; Chung, Moonkyung (Frontiers in Earth Science, 2023)
This study aimed to identify and evaluate the significance of the key design factors that impact the stability of earth retaining wall anchor-supported structures during excavations in urban areas. To this end, finite-element analyses were conducted, and their results were compared and validated with field measurements. These comparisons demonstrated that the numerical modeling technique employed in this study effectively simulates the wall's behavior under excavation conditions. Subsequently, the impact of the main design factors, including ground properties, external conditions, and structural stiffness, on the behavior of the wall was quantitatively assessed by applying variation ratios. The findings indicate that the horizontal displacement of the wall, induced by excavation, is significantly dependent on the unit weight and shear strength of the soil. Conversely, the groundwater level location, surcharge load, and structural stiffness exhibit a relatively minor effect. Finally, the variability of the main design parameters was investigated, considering the specific ground layer where the wall is installed, revealing distinct influences of these variables across different ground layers. Consequently, it is expected that the importance of the influencing geotechnical factors will be selected and used for predicting the behavior of earth retaining walls and actual design, which will help to efficient wall design.